Essays in Political Economy - Gemignani, Thomaz Mingatos Fernandes (2015)
This thesis is divided into three parts. The first part deals with the issue that in a political environment wherein the development of a political career may encompass frequent transitions between offices, it is usually unclear how winning a given position may ultimately affect subsequent electoral performances and career formation. We exploit regression discontinuity designs in Brazilian elections to estimate the electoral advantage derived by incumbents of various positions both when running for reelection to the same held position, and when trying to win a different elective office. Then, we document that incumbency in legislative offices at state and federal levels is associated with a strong positive effect on the probability of winning the same position in the following election, whereas officeholders in diverse branches of local government do not appear to benefit electorally from their incumbency status and may even be harmed by it when they have relatively little political experience. Moreover, we find that state deputies also receive an incumbency advantage when running for the position of federal deputy, and that such a cross-office effect, along with all incumbency effects on winning the same position, is not due to selection into candidacy. Aside from the transition from state deputy to federal deputy, however, incumbents of any position tend to be less likely than their defeated counterparts to run for, and win, other positions. In the second part, we investigate whether incentive-compatible clientelistic transactions may be sustained through the observation of voters\' party-affiliation status by politicians. We argue that since affiliation consists of an instance of public demonstration of support for a given party, vote-buying attempts by parties may be made more effective by targeting voters that are (or in order for them to become) affiliated to them. Using electoral and demographic data on Brazilian municipalities, we find that voters affiliated to parties in the municipal coalition of the Workers\' Party are significantly more likely to start receiving benefits from the Bolsa Família program upon the incumbency of a party in that coalition. We also investigate political determinants of party affiliation and find that while partisan incumbency at the local level appears to affect affiliation only in restricted situations, the provision of payments from the Bolsa Família has a robust positive effect on affiliation. Lastly, the third part investigates the extent to which teachers with strong partisan stances are capable of influencing electoral outcomes through shaping their students\' voting behavior. We address this question by exploiting unique datasets on party-affiliated voters and on public high school teachers in the state of São Paulo, Brazil---through which we are able to identify teachers\' political affiliations. Along with such information, we also make use of very rich datasets on election results and voter characteristics to explore the relationship between the density of affiliated teachers in a given region and electoral outcomes observed for that region. To overcome endogeneity issues such as that of selection in the assignment of teachers to schools and of voters to polling places, for instance, we explore the varying intensity of the hypothesized effect according to electorate characteristics at the polling station level, a very specific site within the polling district to which voters and teachers are suggested not to be able to select themselves. Our results are suggestive of a positive and significant effect of the presence of affiliated teachers on the electoral performance of the corresponding party, especially in elections based on plurality voting systems. However, our evidence also indicates that such an effect is more relevant for (and possibly restricted to) teachers affiliated to the Workers\' Party, and that these teachers appear to be altering political